The comparison in detection of Legionella pneumophila from water in cooling tower between cultivation method and duplex-PCR - Intorasoot, Amornrat; Boonthum, Anusorn; Intorasoot, Sorasak (Biomedical Sciences and Clinical Medicine, 2024)
Objective The objective of this study was the detection of Legionella pneumophila in cooling towers distributed around Maharaj Nakorn Chiang Mai Hospital by comparing the cultivation method with the in house duplex-PCR. Methods Legionella spp. were detected in water sampling from cooling towers in Maharaj Nakorn Chiang Mai Hospital during 2010 by duplex-PCR. The primers using in this study were genus-specific primers and species-specific primers designed from 16sRNA gene and macrophage infectivity potentiator (mip) gene of Legionella spp. and L. pneumophila. The cultivation method was used as gold standard method in this study. Results Legionella were detected in 27 samples from a total of 40 samples by duplex-PCR. From 27 PCR-positive samples, 8 samples were contaminated with L. pneumophila and 19 samples were contaminated with Legionella spp. L. pneumophila were detected in 4 samples by cultivation method while duplex-PCR method showed 3 positive results and 1 negative result from the same samples. In determination of specifi city of PCR primers designed from mip gene, PCR products amplifi ed from Legionella, Salmonella Typhi and Salmonella Enteritidis are similar in size. The direct DNA sequencing of the PCR products showed the similar nucleotide sequences between two Salmonella and mip primers (17/20 nucleotides). Conclusion Duplex-PCR is the convenient and rapid method with high specificity and high sensitivity in the detection of L. pneumophila and Legionella spp. Cultivation method needs at least 3-5 days for Legionella culture and most Legionella shows the variety in biochemical reaction. Therefore, cultivation method is an inappropriate method in Legionella isolation. Nevertheless, detection of both 16s rDNA gene and mip gene in duplex- PCR need to perform together for reducing of false positive result from other bacteria.